What motivates food workers to adhere with WHO guidelines to combat the COVID-19? A social cognitive theory perspective - Wang, Mingliang; Gong, Shunlong; Tang, Jin; Weng, Zhenlin; Wu, Xingtong (Frontiers in Public Health, 2023)
Background COVID-19 has become a public health emergency and pandemic of global concern, and the hundreds of millions of foodborne illnesses that occur each year also wreak havoc on human lives, society and the economy. Promoting workers in food service establishments to adhere to the hygiene practices in the WHO guidelines is a two-birds-one-stone strategy in preventing the spread of COVID-19 and limiting the occurrence of foodborne illness. The aim of this study was to determine the drivers that motivate workers to adhere to hygiene practices based on social cognitive theory. Methods The cross-sectional survey targeting food workers using face-to-face interviews was conducted from July to September 2022. Stratified random sampling and convenience sampling were employed to locate survey sites and respondents, respectively. The survey uses a credible questionnaire evaluated by multiple reliability and validity measures. Binary logistic regression was employed to identify significant determinants of adherence to WHO-initiated hygiene practices. Results A total of 900 workers were interviewed and 609 valid questionnaires were received. The study showed that the average correct rate of knowledge about hygiene practices was only 51.09%, that perceived non-adherence to hygiene practices was most likely to result in lower customer satisfaction and the spread of COVID-19, and that only about 11.7% of the workers always adhered to hygiene practices. Three of the cognitive dimensions in the personal factors, self-efficacy, risk perception, and knowledge, had significant positive effects on adherence practices. Among the demographic variables, there were significant differences in adherence practices differing by income level and place of residence. Conclusion It was found that workers’ knowledge of the WHO-initiated hygiene practices is insufficient and that the frequency of adherence to hygiene practices is poor and require improvement. The significant drivers and effects of demographic variables provide evidence-based guidance to identify priority intervention information and populations to improve worker hygiene practices.